Polifemo in Omero, Euripide, Luciano (Minerva, 2019)
Odysseus’ adventure in the cave of Cyclops —one of the most famous Odyssey’s episodes— has been resumed, in different transpositions, by Euripides in the satyric drama The Cyclops, and by Lucian in one of the Sea dialogues. In this research these three discussions of the myth, with their analogies and differences, are juxtaposed, and the personal approach by each of these authors with Polyphemus’ story is analized.
Keywords: Polyphemus; Homer; Euripides; Lucian; satyric drama; myth